The Effect of Covid-19 Pandemic on the Public Appraisal Services Office (KJPP) Performance - Firmansyah; Maswanto; Prayitno, Irwan (Fakultas Ekonomi dan Bisnis Universitas Mulawarman, 2024)
The aim of this research is to determine the effect of Covid-19 pandemic on the Public Appraisal Services Office (KJPP) performance. The main issue that will be announced in this research is in relation to how big Covid-19 gives effect to KJPP performance. The research method applied is literature review through collecting, identifying, and evaluating the gaining effect of the Covid-19 pandemic towards KJPP performance. Secondary data has been used in this research from the official government websites, and Google Scholar for relevant journals or articles. The phenomenon of Covid-19 leads many changes occurred in any aspects of human beings. That condition has transformed most manual activities of human beings into digital-based activities, where KJPP should implement digital-based assessment procedures to compete and adapt to technological developments nowadays